Low-level maternal exposure to cadmium, lead, and mercury and birth outcomes in a Swedish prospective birth-cohort. (October 2020) - Gustin, Klara; Barman, Malin; Stråvik, Mia; Levi, Michael; Englund-Ögge, Linda; Murray, Fiona; Jacobsson, Bo; Sandberg, Ann-Sofie; Sandin, Anna; Wold, Agnes E.; Vahter, Marie; Kippler, Maria
Abstract: Observational studies have indicated that low-to-moderate exposure to cadmium (Cd), lead (Pb), and mercury (Hg) adversely affects birth anthropometry, but results are inconclusive. The aim of this study was to elucidate potential impact on birth anthropometry of exposure to Cd, Pb, and Hg in pregnant women, and to identify the main dietary sources. In the NICE (Nutritional impact on Immunological maturation during Childhood in relation to the Environment) birth-cohort in northern Sweden, blood and urine were collected from pregnant women in early third trimester. Cd, Pb and Hg were measured in erythrocytes (n = 584), and Cd also in urine (n = 581), by inductively coupled plasma mass spectrometry. Dietary data were collected through a semi-quantitative food frequency questionnaire administered in mid-third trimester. Birth anthropometry data were extracted from hospital records. In multivariable-adjusted spline regression models, a doubling of maternal erythrocyte Cd (median: 0.29 μg/kg) above the spline knot of 0.50 μg/kg was associated with reduced birth weight (B: −191 g; 95% CI: −315,  −68) and length (−0.67 cm; −1.2,  −0.14). The association with birth weight remained when the analysis was restricted to never-smokers. Likewise, a doubling of erythrocyte Hg (median 1.5 μg/kg, mainly MeHg) above 1.0 μg/kg, was associated with decreased birth weight (−59 g; −115,  −3.0), and length (−0.29 cm; −0.54,  −0.047). Maternal Pb (median 11 μg/kg) was unrelated to birth weight and length. Erythrocyte Cd was primarily associated with intake of plant derived foods, Pb with game meat, tea and coffee, and Hg with fish. The results indicated that low-level maternal Cd and Hg exposure were associated with poorer birth anthropometry. Further prospective studies in low-level exposed populations are warranted. Graphical abstract: Image 1 Highlights: Blood cadmium and mercury were inversely associated with birth weight and length. The associations of cadmium and mercury with birth anthropometry were non-linear. Maternal blood cadmium was associated with intake of plant derived foods. Maternal blood lead was linked to game, tea and coffee intake, and mercury to fish. The inverse associations occurred at low levels, prevalent in most populations.